(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
INTRODUCTION Educational performance of children with learning disabilities are impressively not satisfactory as what is expected from them, ultimately that has a lifelong impact on the children affecting academic performances, interpersonal relationships, prospects for employment, marital life in later stage etc. Primary school teachers play a very important role in early recognition of learning disabilities, and contribute in the promotion of mental health of children. The objectives of the study are to assess knowledge on learning disabilities among primary school teachers of Letang Municipality, Morang and to find out the association between level of knowledge and selected demographic variables. METHODOLOGY Descriptive cross-sectional study among primary school teachers was carried out in selected government and private schools of Letang Municipality, Morang. Study populations for the study were primary school teachers, both male and female, who were teaching up to grade five. Proportionate sampling technique was used to select participants from both public and private schools. Self-administered, structured questionnaire was used for data collection. Analysis was done in SPSS version 20.0. Descriptive statistics and inferential statistics (chi-square test) used to find the association between level of knowledge and selected demographic variables. RESULT Among 120 respondents, more than half 65.8% had moderately adequate knowledge, 32.5% had inadequate knowledge and only 1.7% had adequate knowledge on learning disabilities and there was no association between teacher’s level of knowledge on learning disabilities and demographic variables. CONCLUSION The study concluded that more than half of the respondents have average knowledge on learning disabilities. There was no association between age, sex, teaching experience, types of school and training.